Arahan Pengembangan Kawasan Wisata Gunung Nona Berbasis Mitigasi Bencana Tanah Longsor - Sri Utami; Ihsan Ihsan; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2018)
The Mount Nona tourist area is a tourist area in Enrekang Regency. As a tourist area in the mountains, it cannot be denied that this area is prone to disasters, especially landslides. This study aims to identify patterns of development of tourism facilities in the Mount Nona tourism area, identify the level of landslide disaster vulnerability, and compile directions for the development of the Mount Nona tourism area based on landslide disaster mitigation. Data collection techniques in the form of observation, interviews, documentation, and inventory in related agencies. The data analysis techniques used are descriptive qualitative and quantitative analysis, weighting scoring analysis, and spatial analysis. The results of the research show that the tourism facilities in the form of basic facilities are tourism objects, accommodation and restaurants, and complementary facilities in the form of games and photo spots. The pattern of regional development in the range of 1995 - 2012 still follows the main road pattern and began to develop towards the East following the tourist attraction of Buttu Macca in the 2013-2018 range. Mount Nona Tourism Area covers parts of Mandatte Village and Bambapuang Village. The area of ​​area with moderate level of vulnerability in Mandatte Village is 926.60 Ha and the area of ​​hazard is 681.21 Ha. Whereas for Bambapuang Village, the area of ​​medium vulnerability is 1446.26 Ha and prone area is 915.92 Ha. Directions for tourism areas are divided into two zones, for vulnerable zones directed as limited natural tourism areas and can only mitigate disasters with an environmental approach while prone zones are being directed as conditional nature tourism areas and disaster mitigation approaches can be done by means of technical engineering.